An OCT Study of Anterior Nodular Episcleritis and Scleritis. (28th February 2017) - Christakopoulos, Christos
Abstract : Anterior scleritis and episcleritis are a well-known presentation in tuberculosis. The case of a female patient with presumed tuberculous anterior scleritis and episcleritis is discussed in this article. Anterior segment OCT was efficient in diagnosis and evaluation of the therapeutic outcome. Antituberculosis chemotherapy was sufficient to achieve clinical remission.